2018
DOI: 10.1097/md.0000000000011566
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide research productivity in the field of back pain

Abstract: Background:This study aimed to show the world research productivity in the field of back pain and to help researchers follow the scientific development and promote the cooperation in this field.Methods:Web of Science (WoS) database was searched from 1995 to 2016 without other restrictions. The keywords were as follows: “lumbar NEAR pain,” “back pain,” “dorsalgia,” “backache,” “lumbago,” “back NEAR disorder,” and “discitis.” The following information of retrieved articles was analyzed: countries/territories, jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A limitation of this approach is the constant change in these socioeconomic parameters. However, they are commonly used as proxies to relate research productiveness to socioeconomic features (Chong et al 2016;Wang and Zhao 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this approach is the constant change in these socioeconomic parameters. However, they are commonly used as proxies to relate research productiveness to socioeconomic features (Chong et al 2016;Wang and Zhao 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the high incidence of NSLBP, a growing number of researchers have studied NSLBP, and relevant articles have been published in academic journals. Nevertheless, few studies on NSLBP have collected global data and conducted a large-scale retrospective analysis through bibliometrics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the visualization also can excavate valuable information by data-mining technology and display it intuitively [20]. Bibliometric analysis has been widely conducted in various areas, such as neurogenic bladder [21], long noncoding RNA [22], cancer [23], and pain [14,[24][25][26]. Liang et al performed a bibliometric analysis to evaluate the emerging trends and hotspots on the area of acupuncture for LBP from 1997 to 2016 [24].…”
Section: Introductionmentioning
confidence: 99%
“…A study done on worldwide research productivity in the field of back pain found that Harvard University was the most productive institution, followed by the University of Washington. 14 A similar study done on the top 100 cited articles in traumatology showed that an author who tied for most published articles was affiliated with the University of Maryland Medical Center. 15 It was also found that the University of California contributed 34% of the top 100 articles in traumatology.…”
Section: Discussionmentioning
confidence: 90%